Resource degradation, low agricultural productivity, and poverty in sub-Saharan Africa: pathways out of the spiral - Ehui, Simeon K.; Pender, John L. (Wiley, 2005)
Sub‐Saharan Africa (SSA) has the lowest agricultural productivity in the world, while almost half of the population lives below US$1 per day. The biggest development policy challenge is to find appropriate solutions to end hunger and poverty in the region. Building on several years of empirical research conducted in East Africa, this paper identifies potential strategies for sustainable development in this region. In general, the empirical evidence reviewed confirms that different strategies are needed in different development domains of SSA. Nevertheless, some elements will be common to all successful strategies, including assurance of peace and security, a stable macroeconomic environment, provision of incentives through markets where markets function, development of market institutions where they do not, and public and private investment in an appropriate mix of physical, human, natural, and social capital. The differences in strategies across these domains mainly reflect differences in the mix of those investments as influenced by different comparative advantages.